DETEKSI PERUBAHAN TUTUPAN MANGROVE DENGAN MENGGUNAKAN CITRA MULTISENSOR DI SUNGAI LIONG PULAU BENGKALIS - Gilda Pudikasari; Yossi Oktorini; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research has been done on Liong river, located in Bengkalis Island on December 2013 by using ALOS AVNIR-2 2009th and RapidEye 2011th. The aims of this research is to know the mangrove cover change on Liong river start from 2009thuntil 2011th. The research method are red green methode then continued by using classification maximum likelihood method and for the accuracy mapping was evaluated by confusion matrix. The results showed that the mangrove’s cover on Liong river has changed and increase. In 2009 mangrove cover from 792,01 ha and increase becoming 812,61 ha. It showed that the rate of mangrove cover located in Liong river which represent increase of 20,6 ha in two years periode. Keywords: mangrove, satellite imagery, change detection.